Analisa Kandungan Antioksidan Polifenol Pada Buah Tin (Ficus Carica) Dan Buah Anggur Merah (Vitis Vinifera) Dengan Metode 2,2-Diphenyl-1- Picrylhydrazyl (DPPH): Analysis of Antioxidant Content of Polyphenols in Figs (Ficus Carica) and Red Grapes (Vitis Vinifera) Using the 2,2-Diphenyl-1- Picrylhydrazyl (DPPH) Method - Syamsu, Rachmat Faisal; Listin, Nurhalisa; Putra, Fadil Mula; Muchsin, Achmad Harun; Mulyadi, Farah Ekawati (Chakra Brahmanda Lentera Institute, 2026)
Antioxidants play an important role in counteracting free radicals that can damage body cells. Indonesia has a wide variety of natural antioxidant sources, including fig fruit (Ficus carica) and red grapes (Vitis vinifera), which are rich in polyphenol and flavonoid compounds. To determine the antioxidant activity of these fruits, the DPPH method is used because it is simple, rapid, and accurate in measuring the ability of compounds to scavenge free radicals. This study aimed to determine the extraction method for fig fruit (Ficus carica) and red grapes (Vitis vinifera), as well as to analyze the polyphenol antioxidant content of both fruits using the DPPH method. This research was an experimental laboratory study. The results showed that the extraction of fig fruit (Ficus carica) and red grapes (Vitis vinifera) was carried out using the maceration method. This method was chosen because it is simple, easy to perform, requires readily available equipment, and is effective in maintaining the stability of heat-sensitive active compounds, making it suitable for extracting polyphenol compounds. Based on the results of the antioxidant activity test using the DPPH method, the fig fruit extract of the Iraqi variety showed an IC₅₀ value classified as very strong antioxidant activity, while the red grape extract of the Red Globe variety showed an IC₅₀ value classified as strong according to the Blois classification. These results indicate that both fruits contain polyphenol compounds with antioxidant potential, with higher antioxidant activity observed in fig fruit compared to red grapes.